Gender Mainstreaming in PTNU: The Role of PSGA in the Prevention and Handling of Sexual Violence at UNISNU Jepara - Saefudin, Ahmad; Arif, Mahmud; Karwadi, Karwadi (PALASTREN: Jurnal Studi Gender, 2025)
This article aims to examine the strategic role of the Gender and Children Studies Centre (PSGA) in integrating gender perspectives within Nahdlatul Ulama Higher Education Institutions (PTNU), particularly at UNISNU Jepara, as well as efforts to prevent and address sexual violence. This research utilizes a qualitative approach with a case study at PSGA UNISNU Jepara, collecting data through observation, interviews, documentation, and surveys. Based on Judith Butler’s theory of gender performativity, the results indicate that PSGA plays a significant role in promoting gender justice on campus through policy development, advocacy for the formation of the PPKS (Prevention and Handling of Sexual Violence) task force, and the implementation of gender awareness training and assistance for victims. PSGA has become the main driving force in creating a more just and safe campus environment, especially in relation to the prevention and handling of sexual violence. However, PSGA’s involvement in policy planning and evaluation is still sporadic and disorganised. Therefore, PSGA’s institutional position in the campus decision-making structure needs to be strengthened.